Evolution of Actors in the English Teacher Training Process in Chile: 1965-2020; [Evolución de Los Actores del Proceso de Formación de Profesores de Inglés en Chile: 1965-2020] - Rubio-Manriquez, M; Orrego-Ramirez, R; Ubeda-Menichetti, R; Castillo-Ramos, S (Universidad Catolica Silva Henriquez, 2023)
An analysis of the evolution of the training process for English teachers must account for the sociopolitical context in which these training processes are developed, and a characterization of the central agents and aspects in this process, namely, academics, the student of pedagogy, and methodological approaches. This qualitative study aims to analyze the interaction between these agents in the context of the formative processes in the historical periods 1965-1973, 1973-1990, and 1990-2020. The methodology included the application of interviews with a sample of 26 outstanding academics from CRUCH universities in three geographical areas of the country: north, RM, and south of Chile. The results allow us to conclude that there is coherence between the account of the interviewees and the evolution of the academic profile in the periods studied. Despite the changes that have taken place during these three periods, it is observed that academics practically do not allude to the sociopolitical context and that great stability has been maintained in the programs. From the students’ perspective, there is a transition from motivations toward linguistic aspects to motivations related to educational social issues. It was found that the role of students is more conditioned by the sociopolitical context than by the implementation of methodologies and changes in the representation of the academic role. © 2023 Universidad Catolica Silva Henriquez. All rights reserved.
Keywords: English teaching methodology; initial teacher training; pedagogy in English; the role of the academic; the role of the student